Regenerating islet-derived protein 3α: A promising therapy for diabetes. Preliminary data in rodents and in humans. Issue 7 (July 2022) - Le Lay, Aurélie; Philippe, Erwann; Roth, Fanny; Sanchez-Archidona, Ana Rodriguez; Mehl, Florence; Denom, Jessica; Prasad, Rashmi; Asplund, Olof; Hansson, Ola; Ibberson, Mark; Andreelli, Fabrizio; Santoro, Lyse; et al.
Abstract: The aim of our study was to test the hypothesis that administration of Regenerating islet-derived protein 3α (Reg3α), a protein described as having protective effects against oxidative stress and anti-inflammatory activity, could participate in the control of glucose homeostasis and potentially be a new target of interest in the treatment of type 2 diabetes. To that end the recombinant human Reg3α protein was administered for one month in insulin-resistant mice fed high fat diet. We performed glucose and insulin tolerance tests, assayed circulating chemokines in plasma and measured glucose uptake in insulin sensitive tissues. We evidenced an increase in insulin sensitivity during an oral glucose tolerance test in ALF-5755 treated mice vs controls and decreased the pro-inflammatory cytokine C-X-C Motif Chemokine Ligand 5 (CXCL5). We also demonstrated an increase in glucose uptake in skeletal muscle. Finally, correlation studies using human and mouse muscle biopsies showed negative correlation between intramuscular Reg3α mRNA expression (or its murine isoform Reg3γ) and insulin resistance. Thus, we have established the proof of concept that Reg3α could be a novel molecule of interest in the treatment of T2D by increasing insulin sensitivity via a skeletal muscle effect. Abstract : Insulin resistance; Glucose uptake; Skeletal muscles; Type 2 diabetes